Adhesive sheet for temporarily fixing electronic component
By using a stacked light-thermal conversion layer and an adhesive layer in the adhesive sheet for temporary fixing of electronic components, the transmittance of light is solved, and the complexity of laser wavelength selection of photothermal conversion materials in the prior art is achieved. The wide range of light irradiation selective peeling simplifies the process and improves the peeling efficiency and visual recognition.
Patent Information
- Application Number
- CN202380046737.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-13
- Filing Date
- 2023-06-06
- Publication Date
- 2025-01-10
AI Technical Summary
In the prior art, the laser wavelength selection of the photothermal conversion material is complicated, resulting in the manufacturing process of the adhesive sheet for temporary fixing of electronic components and the peelability is insufficient.
Adhesive sheets using a laminated structure, including a first photo-thermal conversion layer and a second photo-thermal conversion layer, combined with an adhesive layer, use polyamide The amine resin, polyester resin or polyether ether ketone resin are used as the first photothermal conversion layer material, and a near-infrared absorber and an ultraviolet absorber are used to ensure high transmittance and high peelability of the photothermal conversion layer.
实现了通过光照射显示出剥离性,并且照射光的选择范围宽的电子部件临时固定用粘合片,简化了制造工序,提高了剥离效率和视觉辨认性。
Smart Images

Figure CN119301735A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an adhesive sheet for temporarily fixing electronic components. Background Art
[0002] In recent years, in order to improve the characteristics of semiconductor devices, the trend of fixing semiconductor chips and sealed resin substrates on hard supporting substrates to implement high-temperature processes has accelerated, centered on fields such as semiconductor packaging. For example, in the RDL formation process for forming circuits on semiconductor packages sealed with black resin, a method of temporarily fixing the processed body flatly on a translucent substrate such as glass and separating the hard substrate after forming the RDL on the processed body has been studied. In such applications, liquid adhesives containing carbon black powder as photothermal conversion materials are widely used. In the technology using photothermal conversion materials, the photothermal conversion material is coated on a translucent substrate to form a photothermal conversion layer, and the processed body is firmly fixed during processing. When peeling, the photothermal conversion layer absorbs the light and converts it into heat to undergo thermal decomposition by irradiation with a laser of a specified wavelength, thereby making it possible to simply separate the processed body from the translucent substrate. However, the liquid adhesive for photothermal conversion needs to change the wavelength of the irradiated laser according to the photothermal conversion material, which complicates the manufacturing process.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent No. 4565804
[0006] Patent Document 2: Japanese Patent No. 4405246
[0007] Patent Document 3: Japanese Patent No. 6980999 Summary of the invention
[0008] Problems to be solved by the invention
[0009] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a pressure-sensitive adhesive sheet for temporarily fixing electronic components which exhibits releasability by light irradiation and has a wide range of selectable light for irradiation.
[0010] Means used to solve problems
[0011] The adhesive sheet for temporarily fixing electronic components of the present invention comprises: a stacked structure A, wherein the stacked structure A comprises a first light-to-heat conversion layer and a second light-to-heat conversion layer arranged on at least one side of the first light-to-heat conversion layer; and an adhesive layer, wherein the adhesive layer is arranged on at least one side of the stacked structure A, and the transmittance of the adhesive sheet for temporarily fixing electronic components at a wavelength of 1032 nm is less than 75%, and the transmittance of the adhesive sheet for temporarily fixing electronic components at a wavelength of 355 nm is less than 50%.
[0012] In one embodiment, the first light-to-heat conversion layer is a layer capable of absorbing ultraviolet rays.
[0013] In one embodiment, the first light-to-heat conversion layer is made of polyimide resin, polyester resin or polyetheretherketone resin.
[0014] In one embodiment, the 5% weight loss temperature of the first light-to-heat conversion layer is above 300°C.
[0015] In one embodiment, the second light-to-heat conversion layer is a layer capable of absorbing near infrared rays.
[0016] In one embodiment, the second light-to-heat conversion layer includes a near infrared absorber.
[0017] In one embodiment, the near infrared absorber is a substance containing tungsten element.
[0018] In one embodiment, the near infrared absorber is a substance containing cesium element.
[0019] In one embodiment, the 5% weight loss temperature of the second light-to-heat conversion layer is above 300°C.
[0020] According to another aspect of the present invention, there is provided a method for treating an electronic component. In the method, the electronic component is placed on the adhesive sheet and then subjected to a predetermined treatment.
[0021] In one embodiment, the above-mentioned processing is grinding, dicing, chip bonding, wire bonding, etching, evaporation, chemical liquid cleaning, molding, redistribution layer formation, through hole formation or device surface protection.
[0022] According to another aspect of the present invention, a method for separating a temporarily fixed electronic component from a support is provided. The method comprises: placing the adhesive sheet for temporarily fixing the electronic component on the support, placing the electronic component on the adhesive sheet for temporarily fixing the electronic component, and then irradiating the adhesive sheet with light to separate the first light-to-heat conversion layer from the second light-to-heat conversion layer.
[0023] In one embodiment, the light is laser.
[0024] In one embodiment, the wavelength of the laser is 800 nm or longer.
[0025] In one embodiment, the wavelength of the laser is 380 nm or less.
[0026] Effects of the Invention
[0027] According to the present invention, it is possible to provide a pressure-sensitive adhesive sheet for temporarily fixing electronic components which exhibits releasability by light irradiation and has a wide selection range of light to be irradiated. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a schematic cross-sectional view of a pressure-sensitive adhesive sheet for temporarily fixing electronic components according to one embodiment of the present invention.
[0029] Figure 2 This is a diagram for explaining a method of using the pressure-sensitive adhesive sheet for temporarily fixing electronic components according to one embodiment of the present invention.
[0030] Figure 3 This is a diagram for explaining a method of using the pressure-sensitive adhesive sheet for temporarily fixing electronic components according to one embodiment of the present invention. DETAILED DESCRIPTION
[0031] A. Overview of adhesive sheets for temporary fixing of electronic components
[0032] Figure 1It is a schematic cross-sectional view of an adhesive sheet for temporarily fixing electronic components according to an embodiment of the present invention. The adhesive sheet 110 for temporarily fixing electronic components comprises: a stacked structure A, the stacked structure A comprises a first light-to-heat conversion layer 10 and a second light-to-heat conversion layer 20 arranged on at least one side of the first light-to-heat conversion layer 10; and an adhesive layer 30, the adhesive layer 30 being arranged on at least one side of the stacked structure A. The light-to-heat conversion layer is a layer that absorbs light of a specified wavelength and converts the light into heat. Through the heat generated by the light-to-heat conversion layer, the light-to-heat conversion layer itself decomposes, or the layer adjacent to the light-to-heat conversion layer decomposes thermally. As a result, the adhesive sheet for temporarily fixing electronic components exhibits peelability. In one embodiment, through the heat generated by the first light-to-heat conversion layer or the second light-to-heat conversion layer, the second light-to-heat conversion layer decomposes thermally to generate gas, the surface shape of the second light-to-heat conversion layer changes, and the first light-to-heat conversion layer and the second light-to-heat conversion layer can be easily separated (peeled off). It should be noted that in this specification, "thermal decomposition" means that a weight loss of 5% or more can be generated by heating at 250°C or above. As long as the effects of the present invention can be obtained, the adhesive sheet for temporarily fixing electronic components may further include other layers. For example, the adhesive sheet 110 may further include another adhesive layer 40 disposed on the first light-to-heat conversion layer 10 side of the stacked structure A. Hereinafter, the adhesive sheet for temporarily fixing electronic components may also be referred to as an adhesive sheet.
[0033] In one embodiment, the first light-to-heat conversion layer and the second light-to-heat conversion layer are directly configured. If the first light-to-heat conversion layer and the second light-to-heat conversion layer are directly configured, when heat is generated in the first light-to-heat conversion layer, the heat is preferably transferred to the second light-to-heat conversion layer, preferably generating gas. "Direct configuration" means that no other layer is configured between the first light-to-heat conversion layer and the second light-to-heat conversion layer, and these layers are in contact.
[0034] The transmittance of light with a wavelength of 1032nm of the above-mentioned adhesive sheet for temporary fixing of electronic components is 75% or less. In addition, the transmittance of light with a wavelength of 600nm of the above-mentioned adhesive sheet for temporary fixing of electronic components is preferably 50% or more. The transmittance of light with a wavelength of 1032nm is preferably 65% or less, more preferably 50% or less, further preferably 40% or less, particularly preferably 30% or less, and most preferably 20% or less. The lower limit of the transmittance of light with a wavelength of 1032nm is, for example, 1% (preferably 0.5%). The transmittance of light with a wavelength of 600nm is more preferably 60% or more, further preferably 70% or more, and particularly preferably 80% or more. The upper limit of the transmittance of light with a wavelength of 600nm is, for example, 90% (preferably 95%). The above-mentioned adhesive sheet for temporary fixing of electronic components is not only able to show peelability by absorbing laser, but also has excellent visual recognition through the adhesive sheet, which is advantageous in this regard.
[0035] The transmittance of light of wavelength 355nm of the adhesive sheet for temporary fixing of electronic components is less than 50%. By adjusting the transmittance of light of wavelength 355nm for the first photothermal conversion layer, the transmittance of light of wavelength 355nm of the adhesive sheet for temporary fixing of electronic components is adjusted to such a range, so that the heating of the first photothermal conversion layer based on UV laser can be achieved, and an adhesive sheet for temporary fixing of electronic components that can exhibit releasability based on UV laser can be obtained. The transmittance of light of wavelength 355nm of the adhesive sheet for temporary fixing of electronic components is more preferably 0% to 30%, and further preferably 0% to 20%. If within such a range, the effect of the present invention becomes significant.
[0036] In one embodiment, a separation method for separating a temporarily fixed electronic component from a support is provided, which comprises: configuring an adhesive sheet for temporarily fixing the electronic component on the support, configuring the electronic component on the adhesive sheet for temporarily fixing the electronic component, and then irradiating light to the light-to-heat conversion layer (the first light-to-heat conversion layer or the second light-to-heat conversion layer) to separate the first light-to-heat conversion layer and the second light-to-heat conversion layer. More details are as follows. In one embodiment, the adhesive sheet for temporarily fixing the electronic component is adhered to the support through the adhesive layer, and the electronic component (such as a semiconductor component such as a semiconductor wafer) is configured on the first light-to-heat conversion layer side for use. In one embodiment, the adhesive sheet can be as follows Figure 2 Proceed as follows. Figure 2 The adhesive sheet 110 shown includes a stacked structure A (first light-to-heat conversion layer / second light-to-heat conversion layer) and an adhesive layer 30 disposed on the second light-to-heat conversion layer 20 side of the stacked structure A. In this embodiment, a second light-to-heat conversion layer capable of absorbing infrared rays is used, and the second light-to-heat conversion layer performs a light-to-heat conversion function.
[0037] (1) The adhesive sheet 110 is disposed on the support 200 so that the adhesive layer 30 side is on the support 200 side, and then the electronic component 300 as the object to be processed is disposed on the side of the adhesive sheet 110 opposite to the support 200 ( Figure 2 (a) The electronic component 300 may be attached to the adhesive sheet 110 via another adhesive layer 40 , for example.
[0038] (2) IR laser (e.g., with a wavelength of 800 nm or more) is irradiated from the side of the support 200 toward the adhesive sheet 110 (substantially the second light-to-heat conversion layer) disposed on the support 200, thereby generating heat in the second light-to-heat conversion layer 20, which is thermally decomposed to generate gas ( Figure 2 (b)).
[0039] (3) As a result, the surface shape of the second light-to-heat conversion layer 20 changes, and the second light-to-heat conversion layer 20 exhibits peelability relative to the first light-to-heat conversion layer 10. As a result, the first light-to-heat conversion layer 10 (the first light-to-heat conversion layer 10 with the electronic component 300) can be peeled off from the support 200 ( Figure 2 (c) As a result, the electronic component 300 can be separated from the support 200 .
[0040] (4) Next, the laminated structure including the adhesive layer 30 and the second light-to-heat conversion layer 20 on the support 200 is peeled off, thereby recovering the clean support 200 with reduced residue ( Figure 2 (d)).
[0041] In another embodiment, the adhesive sheet may be Figure 3 Proceed as follows. Figure 3 The adhesive sheet 110 shown includes a stacked structure A (first light-to-heat conversion layer / second light-to-heat conversion layer) and an adhesive layer 30 disposed on the second light-to-heat conversion layer 20 side of the stacked structure A. In this embodiment, a first light-to-heat conversion layer capable of absorbing ultraviolet rays is used, and the first light-to-heat conversion layer performs a light-to-heat conversion function.
[0042] (1) The adhesive sheet 110 is disposed on the support 200 so that the adhesive layer 30 side is on the support 200 side, and then the electronic component 300 as the object to be processed is disposed on the side of the adhesive sheet 110 opposite to the support 200 ( Figure 3 (a) The electronic component 300 may be attached to the adhesive sheet 110 via another adhesive layer 40 , for example.
[0043] (2) UV laser (e.g., with a wavelength of 380 nm or less) is irradiated from the side of the support 200 toward the adhesive sheet 110 (substantially the first light-to-heat conversion layer) disposed on the support 200, so that the first light-to-heat conversion layer 10 generates heat, thereby thermally decomposing the second light-to-heat conversion layer 20 to generate gas ( Figure 3 (b)).
[0044] (3) As a result, the surface shape of the second light-to-heat conversion layer 20 changes, and the second light-to-heat conversion layer 20 exhibits peelability relative to the first light-to-heat conversion layer 10. As a result, the first light-to-heat conversion layer 10 (the first light-to-heat conversion layer 10 with the electronic component 300) can be peeled off from the support 200 ( Figure 3 (c) As a result, the electronic component 300 can be separated from the support 200 .
[0045] (4) Next, the laminated structure including the adhesive layer 30 and the second light-to-heat conversion layer 20 on the support 200 is peeled off, thereby recovering the clean support 200 with reduced residue ( Figure 3 (d)).
[0046] The pressure-sensitive adhesive sheet having the above-mentioned properties can be obtained, for example, by adding an appropriate near-infrared absorber to the second light-to-heat conversion layer formed of a resin and using a material capable of absorbing UV light as a material constituting the first light-to-heat conversion layer.
[0047] According to the present invention, two types of photothermal conversion layers are formed so that the transmittance of light with a wavelength of 1032 nm is less than 75%, and the transmittance of light with a wavelength of 355 nm is less than 50%. This allows peeling properties to be produced using either infrared or ultraviolet light, thereby obtaining an adhesive sheet for temporarily fixing electronic components having a wide range of choices for irradiated light.
[0048] The adhesive force of the adhesive sheet at 23°C when the adhesive layer is attached to PET is preferably 0.2N / 20mm to 10N / 20mm, and more preferably 3N / 20mm to 8N / 20mm. If it is within such a range, an adhesive sheet suitable for temporary fixing purposes without positional deviation on the support can be obtained. The adhesive force is measured in accordance with JIS Z 0237:2000. Specifically, the thermal decomposition layer is attached to a glass plate (arithmetic mean surface roughness Ra: 10nm±8nm) by making a 2kg roller go back and forth once, and then the adhesive sheet is peeled off and measured under the conditions of a peeling angle of 180° and a peeling speed (pulling speed) of 300mm / min.
[0049] The adhesive strength of the adhesive sheet at 23°C when the adhesive layer is attached to SUS430 is preferably 0.20 N / 20 mm to 10 N / 20 mm, more preferably 3 N / 20 mm to 7 N / 20 mm. Within this range, an adhesive sheet suitable for temporary fixing without positional deviation on a support can be obtained.
[0050] The thickness of the pressure-sensitive adhesive sheet for temporarily fixing electronic components is preferably 10 μm to 500 μm, more preferably 20 μm to 400 μm.
[0051] B. The first light-to-heat conversion layer
[0052] In one embodiment, the first light-to-heat conversion layer may also function as a base material in the adhesive sheet.
[0053] In one embodiment, the first light-to-heat conversion layer is a layer capable of absorbing ultraviolet rays.
[0054] As long as the effect of the present invention can be obtained, the first light-to-heat conversion layer can be composed of any appropriate resin. Preferably, the first light-to-heat conversion layer is composed of a polyimide resin, a polyester resin or a polyetheretherketone resin. Among them, a polyimide resin is preferred. These resins have UV absorption, and if the resin is used, an adhesive sheet that can be peeled off by UV laser can be obtained.
[0055] The thickness of the first light-to-heat conversion layer is preferably 2 μm to 300 μm, more preferably 2 μm to 100 μm, and even more preferably 2 μm to 50 μm.
[0056] In one embodiment, the transmittance of the first light-to-heat conversion layer at a wavelength of 1032 nm is 60% to 95%, preferably 70% to 90%.
[0057] In one embodiment, the transmittance of the first light-to-heat conversion layer at a wavelength of 600 nm is 50% or more, more preferably 60% or more, further preferably 70% or more, and most preferably 80% or more. The upper limit of the transmittance of the first light-to-heat conversion layer at a wavelength of 600 nm is, for example, 95% (preferably 99%).
[0058] In one embodiment, the transmittance of the first light-to-heat conversion layer at a wavelength of 355 nm is preferably 50% or less, more preferably 0% to 20%. Within this range, a pressure-sensitive adhesive sheet that can be peeled off by UV laser can be obtained.
[0059] The tensile modulus of the first light-to-heat conversion layer at 200°C is preferably 5MPa to 2GPa, more preferably 10MPa to 1.8GPa, further preferably 500MPa to 1.8GPa, and particularly preferably 1GPa to 1.5GPa. If within such a range, the gas generated by laser irradiation is preferably blocked by the first light-to-heat conversion layer, and preferably exhibits peelability caused by the shape change of the surface of the second light-to-heat conversion layer. The tensile modulus can be measured using a dynamic viscoelasticity measuring device. The specific measurement method is described below.
[0060] The 5% weight loss temperature of the first photothermal conversion layer is preferably 300°C or more, more preferably 350°C to 650°C, further preferably 380°C to 600°C, and particularly preferably 400°C to 590°C. If it is within this range, an adhesive sheet with excellent heat resistance can be obtained. In addition, the RDL formation process is usually carried out at a temperature below 250°C, so if the 5% weight loss temperature is within the above range, the outgassing from the first photothermal conversion layer (substrate) in the RDL formation process is reduced, and the influence on the electronic components can be reduced to achieve a stable process. In addition, if the 5% weight loss temperature of the first photothermal conversion layer (substrate) is within the above range, it is not easily damaged during laser irradiation, and when the tape (adhesive layer / substrate) is peeled off from the electronic component, the tape can be removed without breaking. The 5% weight loss temperature refers to the temperature at which the weight of the sample to be evaluated is reduced by 5% by weight relative to the dry weight of the sample before heating when the temperature is increased. The 5% weight loss temperature was measured using a differential thermal analyzer under the conditions of a temperature rise of 10°C / min, a nitrogen atmosphere, and a flow rate of 25 ml / min. The dry weight of the sample refers to the weight excluding the water content in the sample.
[0061] C. Second light-to-heat conversion layer
[0062] In one embodiment, the second light-to-heat conversion layer is a layer that can be thermally decomposed and generate gas by applying heat. The applied heat may be heat caused by the heat generated by the second light-to-heat conversion layer or heat caused by the heat generated by the first light-to-heat conversion layer.
[0063] In one embodiment, the second light-to-heat conversion layer is a layer capable of absorbing near infrared rays. In more detail, the transmittance of light of a wavelength of 1032 nm of the second light-to-heat conversion layer is 75% or less, preferably 50% or less, more preferably 40% or less, further preferably 35% or less, and most preferably 20% or less. If it is within such a range, a second light-to-heat conversion layer that preferably absorbs IR laser and easily generates heat can be formed. The lower limit of the transmittance of light of a wavelength of 1032 nm of the second light-to-heat conversion layer is, for example, 5% (preferably 1%).
[0064] In one embodiment, the transmittance of light of a wavelength of 600 nm of the second light-to-heat conversion layer is 50% or more, more preferably 60% or more, further preferably 70% or more, and most preferably 80% or more. If it is within such a range, a second light-to-heat conversion layer that can help improve visual recognition can be formed. The upper limit of the transmittance of light of a wavelength of 600 nm of the second light-to-heat conversion layer is, for example, 90% (preferably 95%).
[0065] In one embodiment, the transmittance of the second light-to-heat conversion layer at a wavelength of 355 nm is preferably 40% or more, more preferably 50% to 95%. If it is within this range, a pressure-sensitive adhesive sheet that can be peeled off by UV laser can be obtained based on the appropriate selection of the first light-to-heat conversion layer that can absorb ultraviolet rays.
[0066] The thickness of the second light-to-heat conversion layer is preferably 1 μm to 100 μm, more preferably 2 μm to 50 μm, further preferably 3 μm to 30 μm, and particularly preferably 5 μm to 20 μm.
[0067] The 5% weight loss temperature of the second light-to-heat conversion layer is preferably above 300°C, more preferably 310°C to 400°C, further preferably 320°C to 380°C, and particularly preferably 330°C to 370°C. If it is within this range, an adhesive sheet with excellent heat resistance can be obtained. In addition, the RDL formation process is usually carried out at a temperature below 250°C, so if the 5% weight loss temperature is within the above range, the outgassing from the second light-to-heat conversion layer in the RDL formation process is reduced, which can reduce the impact on electronic components and achieve a stable process.
[0068] The elastic modulus of the second photothermal conversion layer based on the nanoindentation method is 100 MPa or more, more preferably 200 MPa to 5 GPa, and further preferably 300 MPa to 3 GPa. If it is within such a range, the shape change of the second photothermal conversion layer caused by gas generation preferably occurs during laser irradiation, and excellent peeling properties can be exhibited. The elastic modulus based on the nanoindentation method refers to the elastic modulus obtained by continuously measuring the load and penetration depth of the indenter when the indenter is pressed into the sample during loading and unloading, and the load-indentation depth curve obtained. The elastic modulus based on the nanoindentation method is obtained by numerically processing the displacement-load hysteresis curve obtained by pressing a diamond Berkovich-type (triangular pyramid-type) probe vertically onto the layer of the measured object using the software (triboscan) attached to the measuring device. In this specification, the elastic modulus based on the nanoindentation method refers to the elastic modulus measured by a single indentation method at a specified temperature (25°C) using a nanoindenter (Triboindenter TI-950 manufactured by Hysitron Corporation) under the measurement conditions of an indentation speed of about 500 nm / sec, a pull-out speed of about 500 nm / sec, and an indentation depth of about 100 nm. It should be noted that the elastic modulus of the second light-to-heat conversion layer can be adjusted by the type of material contained in the layer, the structure of the base polymer constituting the material, the type / amount of additives added to the layer, etc.
[0069] In one embodiment, the second light-to-heat conversion layer contains a near-infrared absorber. In one embodiment, the second light-to-heat conversion layer may be a layer in which a near-infrared absorber is contained in a resin. The second light-to-heat conversion layer may be a resin film. The resin film may be, for example, a film in which a near-infrared absorber is contained in a resin (e.g., a single-layer film), or may be a film including a layer containing a predetermined near-infrared absorber (e.g., a printed layer) and a resin layer.
[0070] As the above-mentioned near-infrared absorber, as long as it can impart near-infrared absorptivity and can obtain the effect of the present invention, any appropriate near-infrared absorber can be used in any appropriate amount. As the near-infrared absorber, for example, cesium tungsten oxide, lanthanum hexaboride, tin-doped indium oxide, antimony-doped tin oxide, cyanine compounds, phthalocyanine compounds, dithiol metal complexes, naphthoquinone compounds, diimmonium compounds, azo compounds, etc. can be used. Among them, cesium tungsten oxide or lanthanum hexaboride is preferred, and cesium tungsten oxide is more preferred. If such a near-infrared absorber is used, a second light-to-heat conversion layer can be formed that is excellent in visible light transmittance while being able to absorb near-infrared rays and generate heat.
[0071] It is preferable to use a substance containing tungsten as the near infrared absorber. As a substance containing tungsten, for example, cesium tungsten oxide is preferably used.
[0072] It is preferable to use a substance containing a cesium element as the near infrared absorber. As a substance containing a cesium element, for example, cesium tungsten oxide is preferably used.
[0073] When the second light-to-heat conversion layer includes a resin and a near-infrared absorber, the near-infrared absorber is preferably contained in an amount of 1 to 50 parts by weight, more preferably 3 to 40 parts by weight, and even more preferably 5 to 30 parts by weight relative to 100 parts by weight of the resin. Within this range, a second light-to-heat conversion layer that can preferentially absorb IR laser light can be formed.
[0074] Any appropriate resin may be used as the resin constituting the second light-to-heat conversion layer. Examples of the resin constituting the second light-to-heat conversion layer include acrylic resins, epoxy resins, polyester resins, polystyrene resins, polyimide resins, and polyurethane resins. Among them, acrylic resins are preferred.
[0075] Preferably, the second light-to-heat conversion layer is composed of a cured product of a curable (e.g., active energy ray-curable or thermosetting) resin composition, more preferably a cured product of an active energy ray-curable resin composition, and more preferably a cured product of an acrylic active energy ray-curable resin composition. The second light-to-heat conversion layer formed of a cured product of a curable resin composition is advantageous in terms of excellent heat resistance. In one embodiment, the second light-to-heat conversion layer formed in the form of a cured product of a curable resin composition contains a polymerization initiator. The polymerization initiator is, for example, a photopolymerization initiator or a thermal polymerization initiator. The near-infrared absorber may be contained in a curable resin composition. In one embodiment, the curable resin composition contains a pentaerythritol-based multifunctional (meth)acrylate. If a pentaerythritol-based multifunctional (meth)acrylate is used, a second light-to-heat conversion layer with excellent heat resistance can be formed.
[0076] In one embodiment, as the above-mentioned active energy ray-curable resin composition, an active energy ray-curable resin composition (A1) containing a base polymer as a matrix (or a monomer or oligomer constituting the base polymer) and an active energy ray-reactive compound (monomer or oligomer) is used. In another embodiment, an active energy ray-curable resin composition (A2) containing an active energy ray-reactive polymer as a base polymer is used. In one embodiment, the above-mentioned base polymer has a functional group that can be cleaved by a photopolymerization initiator. As the functional group, for example, a functional group having a carbon-carbon double bond can be listed. As active energy rays, for example, γ rays, ultraviolet rays, visible light, infrared rays (heat rays), radio waves, α rays, β rays, electron rays, plasma flows, ionizing rays, particle beams, etc. are listed. Preferably, ultraviolet rays are used.
[0077] Examples of the base polymer used in the resin composition (A1) include rubber polymers such as natural rubber, polyisobutylene rubber, styrene-butadiene rubber, styrene-isoprene-styrene block copolymer rubber, recycled rubber, butyl rubber, polyisobutylene rubber, nitrile rubber (NBR), etc.; silicone polymers; acrylic polymers, etc. These polymers may be used alone or in combination of two or more. Among them, acrylic polymers are preferred.
[0078] Examples of the acrylic polymer include homopolymers or copolymers of (meth)acrylates such as alkyl (meth)acrylates, cycloalkyl (meth)acrylates, and aryl (meth)acrylates; and copolymers of the (meth)acrylates and other copolymerizable monomers. Specific examples of the alkyl (meth)acrylate include C1-20 alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. Among them, alkyl (meth)acrylates having a linear or branched alkyl group having 4 to 18 carbon atoms can be preferably used.
[0079] As the above-mentioned other copolymerizable monomers, for example, functional group-containing monomers such as carboxyl group-containing monomers, acid anhydride monomers, hydroxyl group-containing monomers, glycidyl group-containing monomers, sulfonic acid group-containing monomers, phosphoric acid group-containing monomers, acrylamide and acrylonitrile can be listed. As carboxyl group-containing monomers, for example, acrylic acid, methacrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid and crotonic acid can be listed. As anhydride monomers, for example, maleic anhydride and itaconic anhydride can be listed. As hydroxyl group-containing monomers, for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate can be listed. As the monomer containing glycidyl group, for example, (meth) glycidyl acrylate and (meth) methyl glycidyl acrylate can be cited. As the monomer containing sulfonic acid group, for example, styrene sulfonic acid, allyl sulfonic acid, 2-(meth) acrylamido-2-methylpropanesulfonic acid, (meth) acrylamidopropanesulfonic acid, (meth) sulfopropyl acrylate and (meth) acryloxynaphthalenesulfonic acid can be cited. As the monomer containing phosphoric acid group, for example, 2-hydroxyethyl acryloyl phosphate can be cited. As acrylamide, for example, N-acryloyl morpholine can be cited. They can be used alone or in combination of two or more. The content ratio of the structural unit derived from the above-mentioned copolymerizable monomer is preferably 60 parts by weight or less, and more preferably 40 parts by weight or less, relative to 100 parts by weight of the base polymer (acrylic polymer).
[0080] In one embodiment, an acrylic monomer having a glass transition temperature of 40°C or more when forming a homopolymer is used as a monomer constituting an acrylic polymer. That is, the acrylic polymer contains a structural unit derived from an acrylic monomer having a glass transition temperature of 40°C or more when forming a homopolymer. As such acrylic monomers, methyl methacrylate, glycidyl methacrylate, isobutyl methacrylate, acrylonitrile, methacrylonitrile, isopropyl acrylamide, acryloyl morpholine, isobornyl acrylate, etc. can be cited. Among them, methyl methacrylate is preferred. If an acrylic polymer containing a structural unit derived from such a monomer is used, stickiness caused by decomposition products caused by laser irradiation can be prevented. The content ratio of the structural unit derived from the acrylic monomer having a glass transition temperature of 40°C or more when forming a homopolymer is preferably 30 to 80 parts by weight, and more preferably 40 to 75 parts by weight relative to 100 parts by weight of the base polymer (acrylic polymer). If within such a range, the above effect becomes significant.
[0081] The acrylic polymer may include a structural unit derived from a multifunctional monomer. If a multifunctional monomer is used, a second light-to-heat conversion layer with excellent heat resistance can be formed. As a multifunctional monomer, for example, hexanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, epoxy (meth)acrylate (ie, polyglycidyl (meth)acrylate), polyester (meth)acrylate and carbamate (meth)acrylate. They can be used alone or in combination of two or more. In the case of a structural unit derived from a multifunctional monomer, the content ratio of the structural unit derived from the above-mentioned multifunctional monomer is preferably 30 parts by weight or more, and more preferably 40 parts by weight or more, relative to 100 parts by weight of the base polymer (acrylic polymer). The upper limit of the content of the structural unit derived from the polyfunctional monomer is preferably 400 parts by weight or less, more preferably 300 parts by weight or less, based on 100 parts by weight of the base polymer (acrylic polymer).
[0082] The weight average molecular weight of the acrylic polymer is preferably 10,000 to 1,500,000, and more preferably 20,000 to 1,000,000. The weight average molecular weight can be measured by GPC (solvent: THF).
[0083] Examples of the active energy ray reactive compound that can be used in the resin composition (A1) include photoreactive monomers or oligomers having a functional group having a polymerizable carbon-carbon multiple bond, such as an acryloyl group, a methacryloyl group, a vinyl group, an allyl group, an ethynyl group, etc. Specific examples of the photoreactive monomer include esters of (meth)acrylic acid and a polyol, such as trimethylolpropane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol monohydroxy penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and polyethylene glycol di(meth)acrylate; polyfunctional urethane (meth)acrylate; epoxy (meth)acrylate; and oligoester (meth)acrylate. In addition, monomers such as methacryloyl isocyanate, 2-methacryloyloxyethyl isocyanate (2-isocyanatoethyl methacrylate), and m-isopropenyl-α,α-dimethylbenzyl isocyanate may also be used. Specific examples of the photoreactive oligomer include dimers to pentamers of the above monomers. The molecular weight of the photoreactive oligomer is preferably 100 to 3,000.
[0084] In one embodiment, the active energy ray-curable resin composition (A1) contains a pentaerythritol-based multifunctional (meth)acrylate as the active energy ray-reactive compound. The pentaerythritol-based multifunctional (meth)acrylate can be obtained by esterifying a part or all of the hydroxyl groups of pentaerythritol or a polymer thereof with a (meth)acrylate. If the pentaerythritol-based multifunctional (meth)acrylate is used as the active energy ray-reactive compound, a second light-to-heat conversion layer having excellent heat resistance can be formed.
[0085] As the active energy ray-reactive compound, a monomer such as epoxidized butadiene, glycidyl methacrylate, acrylamide, vinylsiloxane, or an oligomer composed of the monomer can be used.
[0086] In the resin composition (A1), the active energy ray-reactive compound is contained in an amount of preferably 0.1 to 500 parts by weight, more preferably 5 to 300 parts by weight, and even more preferably 40 to 150 parts by weight, based on 100 parts by weight of the base polymer.
[0087] Examples of the active energy ray-reactive polymer (base polymer) contained in the resin composition (A2) include polymers having functional groups having carbon-carbon multiple bonds, such as acryloyl, methacryloyl, vinyl, allyl, and ethynyl groups. Specific examples of the active energy ray-reactive polymer include polymers composed of polyfunctional (meth)acrylates (for example, polymers containing structural units derived from polyfunctional monomers), photocationic polymerizable polymers, polymers containing cinnamoyl groups, such as polyvinyl cinnamate, diazotized aminophenol novolac resins, and polyacrylamide.
[0088] In one embodiment, an active energy ray reactive polymer is used which is formed by introducing active energy ray polymerizable carbon-carbon multiple bonds into the side chain, main chain and / or main chain terminal of the acrylic polymer. As a method for introducing radiation polymerizable carbon-carbon double bonds into the acrylic polymer, for example, a method of copolymerizing raw material monomers including a monomer having a predetermined functional group (first functional group) to obtain an acrylic polymer, and then subjecting a compound having a predetermined functional group (second functional group) capable of reacting with the first functional group and a radiation polymerizable carbon-carbon double bond to a condensation reaction or an addition reaction with the acrylic polymer while maintaining the radiation polymerizability of the carbon-carbon double bond.
[0089] As a combination of the first functional group and the second functional group, for example, carboxyl and epoxy, epoxy and carboxyl, carboxyl and aziridine, aziridine and carboxyl, hydroxyl and isocyanate, isocyanate and hydroxyl can be cited. Among these combinations, from the perspective of the ease of reaction tracking, the combination of hydroxyl and isocyanate, the combination of isocyanate and hydroxyl is preferred. In addition, when the technical difficulty of making a polymer with a highly reactive isocyanate group is high, from the perspective of the ease of making or obtaining an acrylic polymer, it is more preferred that the first functional group on the acrylic polymer side is a hydroxyl group and the second functional group is an isocyanate. In this case, as an isocyanate compound having both a radiation-polymerizable carbon-carbon double bond and an isocyanate group as a second functional group, for example, methacryloyl isocyanate, 2-methacryloyloxyethyl isocyanate, and m-isopropenyl-α,α-dimethylbenzyl isocyanate can be cited. In addition, as the acrylic polymer having a first functional group, an acrylic polymer containing a structural unit derived from the above-mentioned hydroxyl-containing monomer is preferred, and an acrylic polymer containing a structural unit derived from an ether compound such as 2-hydroxyethyl vinyl ether, 4-hydroxybutyl vinyl ether, and diethylene glycol monovinyl ether is also preferred.
[0090] The resin composition (A2) may further contain the active energy ray-reactive compound (monomer or oligomer).
[0091] In one embodiment, the active energy ray-curable resin composition includes a polymerization initiator. As the polymerization initiator, for example, a photopolymerization initiator or a thermal polymerization initiator can be used, and a photopolymerization initiator is preferred.
[0092] As the photopolymerization initiator, any appropriate initiator can be used. Examples of the photopolymerization initiator include: α-ketoalcohol compounds such as 4-(2-hydroxyethoxy)phenyl(2-hydroxy-2-propyl)ketone, α-hydroxy-α,α'-dimethylacetophenone, 2-methyl-2-hydroxypropiophenone, and 1-hydroxycyclohexylphenylketone; acetophenone compounds such as methoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxyacetophenone, and 2-methyl-1-[4-(methylthio)-phenyl]-2-morpholinopropane-1-one; benzoin ether compounds such as benzoin ethyl ether, benzoin isopropyl ether, and anisole methyl ether; and benzyl dimethyl ether. Ketal compounds such as ketal; aromatic sulfonyl chloride compounds such as 2-naphthalenesulfonyl chloride; photoactive oxime compounds such as 1-phenyl-1,2-propanedione-2-(O-ethoxycarbonyl)oxime; benzophenone compounds such as benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone; thioxanthone compounds such as thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-dichlorothioxanthone, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone; camphorquinone; halogenated ketones; acylphosphine oxides; acylphosphonates, etc. The amount of the photopolymerization initiator used can be set to any appropriate amount.
[0093] In one embodiment, the active energy ray-curable resin composition may include a photosensitizer.
[0094] It is preferred that the active energy ray-curable resin composition contains a crosslinking agent. Examples of the crosslinking agent include isocyanate crosslinking agents, epoxy crosslinking agents, Azoline crosslinking agents, aziridine crosslinking agents, melamine crosslinking agents, peroxide crosslinking agents, urea crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, carbodiimide crosslinking agents, amine crosslinking agents, etc.
[0095] The content of the cross-linking agent is preferably 0.01 to 20 parts by weight relative to 100 parts by weight of the base polymer of the resin composition.
[0096] In one embodiment, an epoxy crosslinking agent is preferably used. If an epoxy crosslinking agent is used, a thermal decomposition layer having a high 5% weight loss temperature after ultraviolet irradiation can be formed. Examples of the epoxy crosslinking agent include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidyl aniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane (manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name "TETRAD C"), 1,6-hexanediol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., trade name "EPOLIGHT 1600"), neopentyl glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., trade name "EPOLIGHT 1500NP"), ethylene glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., trade name "EPOLIGHT 40E"), propylene glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., trade name "EPOLIGHT 70P"), polyethylene glycol diglycidyl ether (manufactured by NOF Corporation, trade name "EPIOLIGHT 1500NP"), and polyoxyethylene glycol diglycidyl ether. E-400”), polypropylene glycol diglycidyl ether (manufactured by NOF Corporation, trade name “EPIOL P-200”), sorbitol polyglycidyl ether (manufactured by Nagase ChemteX Corporation, trade name “DENACOL EX-611”), glycerol polyglycidyl ether (manufactured by Nagase ChemteX Corporation, trade name “DENACOL EX-314”), pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether (manufactured by Nagase ChemteX Corporation, trade name “DENACOL EX-512”), sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, diglycidyl adipate, diglycidyl phthalate, tris(2-hydroxyethyl)isocyanurate triglycidyl, resorcinol diglycidyl ether, bisphenol S diglycidyl ether, epoxy resins having two or more epoxy groups in the molecule, etc. The content of the epoxy crosslinking agent can be set to any appropriate amount according to the desired characteristics, and is typically 0.01 to 10 parts by weight, more preferably 0.05 to 7 parts by weight, relative to 100 parts by weight of the base polymer.
[0097] In one embodiment, an isocyanate crosslinking agent is preferably used. Specific examples of the above-mentioned isocyanate crosslinking agent include: low-order aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, and isophorone diisocyanate; aromatic isocyanates such as 2,4-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, and xylylene diisocyanate; trimethylolpropane / toluene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., trade name "Coronate L"), trimethylolpropane / hexamethylene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., trade name "Coronate HL"), isocyanurate form of hexamethylene diisocyanate (manufactured by Nippon Polyurethane Industry Co., Ltd., trade name "Coronate HX") and other isocyanate adducts, etc. The content of the isocyanate crosslinking agent can be set to any appropriate amount according to the desired properties, and is typically 0.1 to 20 parts by weight, more preferably 0.5 to 10 parts by weight, relative to 100 parts by weight of the base polymer.
[0098] The active energy ray-curable resin composition may further contain any appropriate additives as required. Examples of the additives include active energy ray polymerization accelerators, free radical scavengers, tackifiers, plasticizers (e.g., trimellitic acid ester plasticizers, pyromellitic acid ester plasticizers, etc.), pigments, dyes, fillers, anti-aging agents, conductive materials, antistatic agents, ultraviolet absorbers, light stabilizers, release regulators, softeners, surfactants, flame retardants, antioxidants, etc.
[0099] (Method for forming light-to-heat conversion layer)
[0100] The light-to-heat conversion layer can be manufactured by any appropriate method. The method for forming the light-to-heat conversion layer includes, for example, the following steps: a step (A) of preparing a second light-to-heat conversion layer-forming composition; a step (B) of coating the second light-to-heat conversion layer-forming composition on the first light-to-heat conversion layer; and a step (C) of curing the coating layer of the second light-to-heat conversion layer-forming composition.
[0101] The second photothermal conversion layer forming composition contains a near-infrared absorber. In one embodiment, the second photothermal conversion layer forming composition can be the above-mentioned curable resin composition (preferably the above-mentioned active energy ray curable resin composition) containing the above-mentioned near-infrared absorber. In one embodiment, as the near-infrared absorber, a substance containing a tungsten element and / or a substance containing a cesium element is used. That is, in one embodiment, the second photothermal conversion layer forming composition contains a substance containing a tungsten element and / or a substance containing a cesium element.
[0102] Any appropriate method may be used as a coating method for the second photothermal conversion layer-forming composition, and examples thereof include bar coater coating, air knife coating, gravure coating, gravure reverse coating, reverse roll coating, die lip coating, die coating, dip coating, offset printing, flexographic printing, screen printing, and the like.
[0103] When the second photothermal conversion layer forming composition contains an active energy ray reactive compound, in step (C), the coating layer of the second photothermal conversion layer forming composition is irradiated with active energy rays such as ultraviolet rays. The irradiation conditions can be set to any appropriate conditions depending on the composition of the second photothermal conversion layer forming composition.
[0104] When the second photothermal conversion layer-forming composition is thermosetting, a heat treatment is performed in step (C). The heating conditions can be set to any appropriate conditions according to the composition of the second photothermal conversion layer-forming composition.
[0105] D. Stacked structure A (first light-to-heat conversion layer / second light-to-heat conversion layer)
[0106] The transmittance of the laminated structure A having the first light-to-heat conversion layer and the second light-to-heat conversion layer at a wavelength of 1032 nm is preferably 75% or less, more preferably 65% or less, further preferably 50% or less, further preferably 40% or less, particularly preferably 30% or less, and most preferably 20% or less. If it is within this range, an adhesive sheet that can preferably absorb IR laser light can be obtained.
[0107] The transmittance of the light with a wavelength of 600 nm of the above-mentioned laminated structure A is preferably 50% or more, more preferably 60% or more, further preferably 70% or more, and particularly preferably 80% or more. The upper limit of the transmittance of the light with a wavelength of 600 nm is, for example, 90% (preferably 95%). The adhesive sheet having such a laminated structure A is advantageous in that it can not only absorb IR laser and generate heat, but also has excellent visual recognition through the adhesive sheet.
[0108] In one embodiment, the transmittance of light with a wavelength of 355 nm of the stacked structure A is 50% or less, preferably 40% or less, more preferably 20% or less, particularly preferably 10% or less, and most preferably 0%. By adjusting the transmittance of light with a wavelength of 355 nm for the first light-to-heat conversion layer, the transmittance of light with a wavelength of 355 nm of the stacked structure A is adjusted to such a range, heat generation of the first light-to-heat conversion layer based on UV laser can be achieved, and an adhesive sheet that can also exhibit releasability based on UV laser can be obtained.
[0109] The thickness of the laminated structure A is preferably 10 μm to 200 μm, more preferably 20 μm to 150 μm.
[0110] E. Adhesive layer
[0111] The adhesive layer includes any appropriate adhesive. For example, it includes a pressure-sensitive adhesive or a curable adhesive. As the curable adhesive, the active energy ray-curable resin composition can be used. The adhesive layer can be formed by applying an adhesive on the stacked structure A (first light-to-heat conversion layer / second light-to-heat conversion layer) using any appropriate method.
[0112] Examples of the adhesive include acrylic adhesives, silicone adhesives, epoxy adhesives, styrene thermoplastic elastomers, and ester adhesives. In one embodiment, an acrylic adhesive is used. Examples of the acrylic adhesive are described below.
[0113] (Base polymer)
[0114] Examples of the acrylic pressure-sensitive adhesive include those using, as a base polymer, an acrylic polymer (homopolymer or copolymer) using one or more kinds of (meth)acrylic acid alkyl esters as monomer components. Specific examples of the alkyl (meth)acrylate include C1-20 alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. Among them, it is preferable to use an alkyl (meth)acrylate having a linear or branched alkyl group having 4 to 18 carbon atoms. In the acrylic polymer, the content ratio of the structural unit of the alkyl (meth)acrylate is preferably 70 to 100 parts by weight, more preferably 75 to 99.9 parts by weight, and further preferably 80 to 99.9 parts by weight, based on 100 parts by weight of the acrylic polymer.
[0115] The acrylic polymer may contain a structural unit derived from another monomer copolymerizable with the (meth)acrylic acid alkyl ester as required in order to improve cohesive force, heat resistance, crosslinking property, etc., to enhance dimensional stability of the adhesive layer, etc. Examples of such monomers include the following monomers.
[0116] Carboxyl-containing monomers: such as ethylenically unsaturated monocarboxylic acids such as acrylic acid (AA), methacrylic acid (MAA), and crotonic acid; ethylenically unsaturated dicarboxylic acids such as maleic acid, itaconic acid, and citraconic acid, and their anhydrides (maleic anhydride, itaconic anhydride, etc.);
[0117] Hydroxyl-containing monomers: for example, hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, etc.; unsaturated alcohols such as vinyl alcohol and allyl alcohol; ether compounds such as 2-hydroxyethyl vinyl ether, 4-hydroxybutyl vinyl ether, and diethylene glycol monovinyl ether;
[0118] Amino-containing monomers: for example, aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, tert-butylaminoethyl (meth)acrylate;
[0119] Epoxy-containing monomers: such as glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, allyl glycidyl ether;
[0120] Cyano-containing monomers: such as acrylonitrile and methacrylonitrile;
[0121] Ketone-containing monomers: for example, diacetone (meth) acrylamide, diacetone (meth) acrylate, vinyl methyl ketone, vinyl ethyl ketone, allyl acetoacetate, vinyl acetoacetate;
[0122] Monomers having a nitrogen atom-containing ring: for example, N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyl oxazole, N-vinylmorpholine, N-vinylcaprolactam, N-(meth)acryloylmorpholine;
[0123] Alkoxysilyl-containing monomers: for example, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane;
[0124] Isocyanate-containing monomers: (meth)acryloyl isocyanate, 2-(meth)acryloyloxyethyl isocyanate, m-isopropenyl-α,α-dimethylbenzyl isocyanate.
[0125] These monomers can be used alone or in combination of two or more.
[0126] The weight average molecular weight of the acrylic polymer is preferably 600,000 to 1,600,000, and more preferably 800,000 to 1,500,000. Within this range, an adhesive layer having excellent heat resistance and dimensional stability at high temperatures and suppressing outgassing caused by heating can be formed. The weight average molecular weight can be measured by GPC (solvent: THF).
[0127] (additive)
[0128] The acrylic adhesive may contain any appropriate additives as required. Examples of the additives include crosslinking agents, crosslinking catalysts, tackifiers, plasticizers, pigments, dyes, fillers, anti-aging agents, conductive materials, antistatic agents, ultraviolet light absorbers, light stabilizers, release regulators, softeners, surfactants, flame retardants, antioxidants, and the like.
[0129] Examples of the crosslinking agent include isocyanate crosslinking agents, epoxy crosslinking agents, melamine crosslinking agents, peroxide crosslinking agents, urea crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, carbodiimide crosslinking agents, Oxazoline crosslinking agents, aziridine crosslinking agents, amine crosslinking agents, etc. Among them, epoxy crosslinking agents or isocyanate crosslinking agents are preferred.
[0130] Examples of the epoxy crosslinking agent include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidyl aniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane (manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name "TETRAD C"), 1,6-hexanediol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., trade name "EPOLIGHT 1600"), neopentyl glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., trade name "EPOLIGHT 1500NP"), ethylene glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., trade name "EPOLIGHT 40E"), propylene glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., trade name "EPOLIGHT 70P"), polyethylene glycol diglycidyl ether (manufactured by NOF Corporation, trade name "EPIOLIGHT 1600"), and polyoxyethylene glycol diglycidyl ether. E-400”), polypropylene glycol diglycidyl ether (manufactured by NOF Corporation, trade name “EPIOL P-200”), sorbitol polyglycidyl ether (manufactured by Nagase ChemteX Corporation, trade name “DENACOL EX-611”), glycerol polyglycidyl ether (manufactured by Nagase ChemteX Corporation, trade name “DENACOL EX-314”), pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether (manufactured by Nagase ChemteX Corporation, trade name “DENACOL EX-512”), sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, diglycidyl adipate, diglycidyl phthalate, tris(2-hydroxyethyl)isocyanurate triglycidyl, resorcinol diglycidyl ether, bisphenol S diglycidyl ether, epoxy resins having two or more epoxy groups in the molecule, etc. The content of the epoxy crosslinking agent can be set to any appropriate amount depending on the desired adhesive force, viscoelasticity, dimensional stability, and gas release of the adhesive layer, and is typically 0.01 to 10 parts by weight, and more preferably 0.03 to 7 parts by weight, relative to 100 parts by weight of the base polymer.
[0131] Specific examples of the isocyanate crosslinking agent include lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, and isophorone diisocyanate; aromatic isocyanates such as 2,4-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, and xylylene diisocyanate; isocyanate adducts such as trimethylolpropane / toluene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industries, Ltd., trade name "Coronate L"), trimethylolpropane / hexamethylene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industries, Ltd., trade name "Coronate HL"), and isocyanurate form of hexamethylene diisocyanate (manufactured by Nippon Polyurethane Industries, Ltd., trade name "Coronate HX"), etc. The content of the isocyanate crosslinking agent can be set to any appropriate amount depending on the desired adhesive force, elasticity of the adhesive layer, dimensional stability, gas release, etc., and is typically 0.1 to 20 parts by weight, more preferably 0.5 to 10 parts by weight, relative to 100 parts by weight of the base polymer.
[0132] In one embodiment, a heat-resistant adhesive is used as the adhesive contained in the adhesive layer. By providing an adhesive layer composed of a heat-resistant adhesive, it is possible to suppress burning (paste residue) on the light-transmitting support substrate when irradiated with laser. In this specification, a heat-resistant adhesive refers to an adhesive having a predetermined adhesive force under an environment of 260° C. The heat-resistant adhesive is preferably capable of being used without paste residue under an environment of 260° C. Preferably, the heat-resistant adhesive contains an acrylic resin, a silicone resin, or the like as a base polymer.
[0133] The thickness of the adhesive layer is preferably 5 μm to 100 μm, more preferably 10 μm to 50 μm.
[0134] The transmittance of the adhesive layer at a wavelength of 1032 nm is preferably 75% or more, more preferably 85% or more, and further preferably 90% or more. The upper limit of the transmittance at a wavelength of 1032 nm is, for example, 97% (preferably 98%).
[0135] The transmittance of the pressure-sensitive adhesive layer at a wavelength of 600 nm is preferably 75% or more, more preferably 85% or more, and even more preferably 90% or more. The upper limit of the transmittance at a wavelength of 600 nm is, for example, 97% (preferably 98%).
[0136] The transmittance of the pressure-sensitive adhesive layer at a wavelength of 355 nm is preferably 75% or more, more preferably 85% or more, and even more preferably 90% or more. The upper limit of the transmittance at a wavelength of 355 nm is, for example, 97% (preferably 98%).
[0137] F. Use of adhesive sheets for temporary fixing of electronic components
[0138] The adhesive sheet for temporary fixing of electronic components can be used as in item A. Figure 2 and Figure 3 Use as described.
[0139] Regarding the electronic component as the object to be processed, for example, there can be listed: semiconductor wafer, semiconductor package, semiconductor chip, insulating material for circuit substrate, chip attach film, semiconductor package resin, semiconductor protective film, resin composition for forming semiconductor protective film, metal material, ceramic material, etc. The above electronic component can be arranged in plurality or in a single piece.
[0140] The electronic component may be attached to the adhesive sheet via another adhesive layer disposed on the side of the first light-to-heat conversion layer opposite to the second light-to-heat conversion layer, for example.
[0141] As the above-mentioned support, a support made of any appropriate material can be used. For example, a support made of glass such as borosilicate glass and quartz glass; sapphire; acrylic resin such as PMMA (polymethyl methacrylate), PC (polycarbonate), etc. is used. In one embodiment, a support having no organic layer on the surface is used. The arithmetic surface roughness Ra of the support is, for example, 0.3nm to 100nm, and more preferably 0.4nm to 50nm. The arithmetic surface roughness Ra can be measured according to JISB 0601. Generally, from the viewpoint of preventing residue, it is preferred that the surface roughness of the support is small. In addition, the above-mentioned support is preferably translucent in the range of ultraviolet to infrared. It is particularly preferred to be translucent to a laser of any selected wavelength. The transmittance of the support at the wavelength of the laser is, for example, 50% or more, and more preferably 60% or more. The water contact angle on the surface of the support is, for example, 0° to 150°, and more preferably 3° to 120°. According to the present invention, even when using a support that has been difficult to peel well (eg, residue generation, poor pickup properties), better peeling can be achieved, that is, the range of choices for the support is widened, which is advantageous.
[0142] After the electronic components are arranged on the above-mentioned adhesive sheet (ie, Figure 2 (a) state), the electronic component may be subjected to a predetermined process. Examples of such processes include grinding, dicing, chip bonding, wire bonding, etching, chemical liquid cleaning, vapor deposition, molding, redistribution layer formation, through hole formation, or device surface protection.
[0143] As the above-mentioned laser, a laser of any appropriate wavelength is used according to the composition of the adhesive sheet. The conditions for laser irradiation can also be set to any appropriate conditions according to the composition of the adhesive sheet. In one embodiment, an IR laser is used as the above-mentioned laser. The wavelength of the IR laser is preferably above 800nm, more preferably 800nm to 1600nm, and further preferably 900nm to 1200nm. The output power of the IR laser is, for example, 0.01W to 10W. In another embodiment, a UV laser is used as the above-mentioned laser. The wavelength of the UV laser is preferably below 380nm, more preferably 150nm to 380nm, and further preferably 240nm to 360nm. The output power of the UV laser is, for example, 0.1W to 2.0W. It should be noted that when the first light-to-heat conversion layer can absorb the UV laser, a UV laser can be selected. When the UV laser is irradiated, the second light-to-heat conversion layer is thermally decomposed by the heat generated by the first light-to-heat conversion layer, thereby exhibiting peelability.
[0144] Example
[0145] The present invention will be specifically described below by way of examples, but the present invention is not limited to these examples. The evaluation methods in the examples are as follows. In addition, in the examples, "parts" and "%" are by weight unless otherwise specified.
[0146] [evaluate]
[0147] (1) Tensile elastic modulus of the first light-to-heat conversion layer (substrate) at 200°C
[0148] The tensile modulus at 200° C. was measured under the following conditions using a dynamic viscoelasticity measuring apparatus (manufactured by TA Instruments, trade name “RSA-3”).
[0149] Measuring frequency: 1Hz
[0150] Strain: 0.05%
[0151] Distance between chucks: 20mm
[0152] Sample width: 10mm
[0153] The heating rate from 0°C to 250°C is 5°C / min
[0154] (2) 5% weight loss temperature of the first light-to-heat conversion layer (substrate), the second light-to-heat conversion layer and the stacked structure A
[0155] A differential thermal analyzer (manufactured by TA Instruments, trade name “Discovery TGA”) was used and set to a heating temperature of 10°C / min, N 2The temperature at which the weight of a given sample decreases by 5% relative to the dry weight of the sample before the temperature increase is measured under a temperature-controlled atmosphere and at a flow rate of 25 ml / min. The dry weight of the sample refers to the weight excluding the water in the sample.
[0156] Specifically, about 0.01 g of the evaluation sample is placed in the analysis device, and the temperature is first raised from 20°C to 110°C at the above-mentioned heating rate, and then lowered from 110°C to 20°C at a cooling rate of 10°C / min, thereby removing the influence of the contained water and obtaining the dry weight. The temperature is again raised from 20°C to 500°C at the above-mentioned heating rate, and the weight loss of the evaluation sample is measured. The temperature at which the weight loss is 5% is extracted from the obtained data.
[0157] (3) Light transmittance of laminated structure A, adhesive sheet, and adhesive layer
[0158] The spectrophotometer (trade name "UV-VIS UV Visible Spectrophotometer SolidSpec 3700", manufactured by Shimadzu Corporation) was set up to allow incident light to be incident vertically on each sample, and the transmittance in the wavelength range of 300nm to 2500nm was measured. The transmittance at wavelengths of 355nm, 600nm, and 1032nm was extracted from the obtained transmission spectrum.
[0159] (4) Evaluation of laser debonding using IR laser
[0160] The adhesive layer (thickness: 10 μm) on the first photothermal conversion layer (substrate) side of the adhesive sheet was attached to a thin glass (cover glass, rectangular No. 1, trade name "C050701" manufactured by Matsunami Glass) with a width of 50 mm, a length of 70 mm, and a thickness of 0.12 mmt, which simulates a workpiece such as a semiconductor wafer, using a hand roller. The adhesive sheet was cut according to the size of the thin glass, and then the adhesive layer (thickness: 30 μm, 1032 nm light transmittance: 93.91%) on the second photothermal conversion layer side was laminated on a support (thick glass (large slide glass, standard large white edge grinding No. 2, trade name "S9112" manufactured by Matsunami Glass) with a width of 52 mm, a length of 76 mm, and a thickness of 1.0 mmt, which simulates a light-transmitting support substrate) using a hand roller. Then, the laminate was placed in an autoclave for heating and degassing (40°C, 5 kgf, 10 minutes) to remove bubbles trapped in the laminate, thereby preparing a laminate sample.
[0161] The prepared laminated body sample was irradiated with laser from the support side, and the laser debonding property evaluation was implemented. Specifically, a laser with a wavelength of 1032nm and a beam diameter of about 200μmφ was used, and pulse scanning was performed at an output power of 8.4W and a frequency of 25kHz at intervals of about 60μm in the vertical and horizontal directions. After the laminated body sample was irradiated with laser, the bonding property was evaluated by the following benchmarks.
[0162] Regarding the evaluation of laser debonding properties, in the debonding operation of thin glass and thick glass, the level at which debonding can be easily performed when one point of the outer periphery of the laminated body sample is lifted up by a cutting knife is evaluated as qualified debonding operation performance (○), the level at which debonding can be finally performed after the entire outer periphery is lifted up by a cutting knife is evaluated as △, and the level at which debonding cannot be performed even if the cutting knife is inserted into the outer periphery and the thin glass (processed body) is broken is evaluated as unqualified (×).
[0163] (5) Laser debonding evaluation using UV laser
[0164] A laminate sample was obtained in the same manner as in the above evaluation (4).
[0165] The prepared laminate sample was irradiated with laser from the support side to evaluate the laser debonding property. Specifically, a wavelength of 355 nm, a beam width of about 10 μm, a beam length of about 1.5 mm, and an energy density of 0.5 J / cm 2 The line laser was pulse scanned at an output power of 0.75 W and a frequency of 10 kHz in such a way that the interval between the line centers produced an overlap of about 10 μm in the width direction and an overlap of about 0.2 mm or more in the length direction.
[0166] (6) Chemical resistance
[0167] 0.1 mL of N-methyl-2-pyrrolidone (manufactured by Kishida Chemical Co., Ltd.) was dropped onto the second light-to-heat conversion layer, and then the layer was left at 25°C for 15 minutes. The N-methyl-2-pyrrolidone (manufactured by Kishida Chemical Co., Ltd.) was wiped off, and the chemical liquid resistance was evaluated based on whether the second light-to-heat conversion layer peeled off. In the table, the case where there was no peeling off was recorded as passing (O), and the case where there was peeling off was recorded as failing (×).
[0168] (7) Visual recognizability
[0169] The visibility through the adhesive sheet was evaluated. Specifically, the visibility was evaluated based on whether the chip could be visually recognized through the adhesive sheet under a fluorescent light. The case where the chip could be visually recognized was rated as pass (0), and the case where the chip could not be visually recognized was rated as fail (×).
[0170] [Manufacturing Example 1] Second Photothermal Conversion Layer Forming Composition A
[0171] A composition A for forming a light-to-heat conversion layer was prepared by mixing 50 parts by weight of an acrylic polymer having a weight average molecular weight (Mw) of about 22,000 obtained by copolymerizing methyl methacrylate and acryl-modified glycidyl methacrylate at a ratio of 50:50 (molar ratio), 50 parts by weight of a pentaerythritol-based multifunctional acrylate, methyl isobutyl ketone, 0.5 parts by weight of a photopolymerization initiator (manufactured by BASF, trade name "Omnirad 127D"), 15 parts by weight of a near-infrared absorber (cesium tungsten oxide dispersion, trade name "YMF-02A", manufactured by Sumitomo Metal Mining Co., Ltd.), and ethyl acetate.
[0172] [Manufacturing Example 2] Second Photothermal Conversion Layer Forming Composition B
[0173] A second light-to-heat conversion layer-forming composition B was prepared in the same manner as in Production Example 1 except that the blending amount of the infrared absorber (cesium tungsten oxide dispersion, trade name “YMF-02A”, manufactured by Sumitomo Metal Mining Co., Ltd.) was adjusted to 7.5 parts by weight.
[0174] [Manufacturing Example 3] Second Photothermal Conversion Layer Forming Composition C
[0175] A second light-to-heat conversion layer-forming composition C was prepared in the same manner as in Production Example 1 except that the amount of the infrared absorber (cesium tungsten oxide dispersion, trade name “YMF-02A”, manufactured by Sumitomo Metal Mining Co., Ltd.) was adjusted to 23 parts by weight.
[0176] [Manufacturing Example 4] Second Photothermal Conversion Layer Forming Composition D
[0177] 50 parts by weight of an acrylic polymer having a weight average molecular weight (Mw) of about 22,000 obtained by copolymerizing methyl methacrylate and acryl-modified glycidyl methacrylate at a ratio of 50:50 (molar ratio), 50 parts by weight of a pentaerythritol-based multifunctional acrylate, methyl isobutyl ketone, 10 parts by weight of an acrylic polymer having a weight average molecular weight (Mw) of about 29,000 obtained by copolymerizing methyl methacrylate and acryl-modified glycidyl methacrylate at a ratio of 71:29 (molar ratio), butyl acetate, 0.5 parts by weight of a photopolymerization initiator (manufactured by BASF, trade name “Omnirad 127D”), 15 parts by weight of a near infrared absorber (cesium tungsten oxide dispersion, trade name “YMF-02A”, manufactured by Sumitomo Metal Mining Co., Ltd.), and ethyl acetate were mixed to prepare a composition D for forming a light-to-heat conversion layer.
[0178] [Manufacturing Example 5] Second Photothermal Conversion Layer Forming Composition E
[0179] A composition E for forming a light-to-heat conversion layer was prepared in the same manner as in Production Example 4, except that the amount of “an acrylic polymer having a weight average molecular weight (Mw) of about 29,000 obtained by copolymerizing methyl methacrylate and acryl-modified glycidyl methacrylate at a ratio of 71:29 (molar ratio)” was adjusted to 40 parts by weight.
[0180] [Manufacturing Example 6] Second Photothermal Conversion Layer Forming Composition F
[0181] 100 parts by weight of an acrylic polymer having a weight average molecular weight (Mw) of about 29,000 obtained by copolymerizing methyl methacrylate and acryl-modified glycidyl methacrylate at a ratio of 71:29 (molar ratio), butyl acetate, 0.5 parts by weight of a photopolymerization initiator (manufactured by BASF, trade name "Omnirad 127D"), 15 parts by weight of a near-infrared absorber (cesium tungsten oxide dispersion, trade name "YMF-02A", manufactured by Sumitomo Metal Mining Co., Ltd.), and ethyl acetate were mixed to prepare a composition F for forming a light-to-heat conversion layer.
[0182] [Manufacturing Example 7] Second Photothermal Conversion Layer Forming Composition G
[0183] A second photothermal conversion layer-forming composition G was prepared in the same manner as in Production Example 1 except that the amount of the infrared absorber (cesium tungsten oxide dispersion, trade name “YMF-02A”, manufactured by Sumitomo Metal Mining Co., Ltd.) was adjusted to 4 parts by weight.
[0184] [Example 1]
[0185] The second photothermal conversion layer-forming composition A obtained in Manufacturing Example 1 was applied to one side of a polyimide film (manufactured by DuPont Toray Industries, trade name “Kapton 100H”, thickness: 25 μm) in such a manner that the thickness after the solvent was volatilized (dried) was 2 μm, and then dried to form a second photothermal conversion layer on the polyimide film. A polyethylene terephthalate film with a silicone release agent-treated surface (manufactured by Toray Industries, Ltd., trade name “Cerapeel”, thickness: 38 μm) was laminated between rolls to form a second photothermal conversion layer. The accumulated light intensity was 1380 mJ / cm from the polyethylene terephthalate film side with the silicone release agent-treated surface. 2 UV irradiation was performed under the condition of . Then, the polyethylene terephthalate film with the silicone release agent treated surface was peeled off to obtain a laminate (second light-to-heat conversion layer / first light-to-heat conversion layer (base material: polyimide film)).
[0186] An adhesive was applied to the first light-to-heat conversion layer (substrate) side of the laminate to form an adhesive layer with a thickness of 10 μm. In addition, an adhesive was applied to the second light-to-heat conversion layer side of the laminate to form an adhesive layer with a thickness of 30 μm. The adhesive sheet obtained in this way was subjected to the above evaluation. The results are shown in Table 1.
[0187] It should be noted that the adhesive forming the adhesive layer on the first photothermal conversion layer (substrate) side and the adhesive forming the adhesive layer on the second photothermal conversion layer side are prepared as follows. That is, 95 parts by weight of 2-ethylhexyl acrylate, 5 parts by weight of acrylic acid, and 0.15 parts by weight of benzoyl peroxide as a polymerization initiator are added to ethyl acetate, and then heated to 70°C to obtain an ethyl acetate solution of an acrylic polymer (polymer A). Then, 0.4 parts by weight of an epoxy crosslinking agent (manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name "TETRAD C") is added to the ethyl acetate solution to obtain an adhesive for the adhesive layer on the second photothermal conversion layer side. In addition, 2 parts by weight of an epoxy crosslinking agent (manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name "TETRAD C") is added to the above-mentioned ethyl acetate solution to obtain an adhesive for the adhesive layer on the first photothermal conversion layer (substrate) side.
[0188] The transmittance of the adhesive layer on the second light-to-heat conversion layer side for light with a wavelength of 355 nm was 91.1%, the transmittance for light with a wavelength of 600 nm was 92.8%, and the transmittance for light with a wavelength of 1032 nm was 93.91%.
[0189] [Example 2 to Example 4]
[0190] A pressure-sensitive adhesive sheet was produced in the same manner as in Example 1 except that the thickness of the second light-to-heat conversion layer was adjusted to be as described in Table 1. The obtained pressure-sensitive adhesive sheet was subjected to the above-mentioned evaluation. The results are shown in Table 1.
[0191] [Example 5]
[0192] A pressure-sensitive adhesive sheet was produced in the same manner as in Example 1 except that the second light-to-heat conversion layer-forming composition B was used instead of the second light-to-heat conversion layer-forming composition A and the thickness of the second light-to-heat conversion layer was adjusted to 5 μm. The obtained pressure-sensitive adhesive sheet was subjected to the above evaluation. The results are shown in Table 1.
[0193] [Example 6]
[0194] A pressure-sensitive adhesive sheet was produced in the same manner as in Example 1 except that the second light-to-heat conversion layer-forming composition C was used instead of the second light-to-heat conversion layer-forming composition A and the thickness of the second light-to-heat conversion layer was adjusted to 20 μm. The obtained pressure-sensitive adhesive sheet was subjected to the above evaluation. The results are shown in Table 1.
[0195] [Example 7]
[0196] A polyethylene terephthalate film (manufactured by Toray Industries, Ltd., trade name "Lumirror S27", thickness: 38 μm) was used instead of a polyimide film (manufactured by DuPont Toray Industries, Ltd., trade name "Kapton 100H", thickness: 25 μm), and the thickness of the second light-to-heat conversion layer was adjusted to 5 μm. The same operation as in Example 1 was performed to produce an adhesive sheet. The obtained adhesive sheet was subjected to the above evaluation. The results are shown in Table 2.
[0197] [Example 8]
[0198] A pressure-sensitive adhesive sheet was produced in the same manner as in Example 7 except that the second light-to-heat conversion layer-forming composition F was used instead of the second light-to-heat conversion layer-forming composition A. The obtained pressure-sensitive adhesive sheet was subjected to the above-mentioned evaluation. The results are shown in Table 2.
[0199] [Example 9]
[0200] A polyethylene naphthalate film (manufactured by Teijin Film Solutions Co., Ltd., trade name "Teonex (registered trademark) Film Q51C-50", thickness: 50 μm) was used instead of a polyimide film (manufactured by DuPont Toray Co., Ltd., trade name "Kapton 100H", thickness: 25 μm), and the thickness of the second light-to-heat conversion layer was adjusted to 5 μm. The same operation as in Example 1 was performed to produce an adhesive sheet. The obtained adhesive sheet was subjected to the above evaluation. The results are shown in Table 2.
[0201] [Example 10]
[0202] A polyetheretherketone film (manufactured by KURABO Co., Ltd., trade name "EXPEEK", thickness: 12 μm) was used instead of a polyimide film (manufactured by DuPont Toray Co., Ltd., trade name "Kapton 100H", thickness: 25 μm) and the thickness of the second light-to-heat conversion layer was adjusted to 5 μm. The same operation as in Example 1 was performed to produce an adhesive sheet. The obtained adhesive sheet was subjected to the above evaluation. The results are shown in Table 2.
[0203] [Comparative Example 1]
[0204] Adhesive layers (thickness: 10 μm, 30 μm) were formed on both sides of a polyimide film (manufactured by DuPont Toray Co., Ltd., trade name: "Kapton 100H", thickness: 25 μm) to obtain an adhesive sheet. The obtained adhesive sheet was subjected to the above evaluation. The results are shown in Table 3.
[0205] [Comparative Example 2]
[0206] An adhesive layer (thickness: 10 μm, 30 μm) was formed on both sides of a polyethylene terephthalate film (manufactured by Toray Industries, Inc., trade name: Lumirror S27, thickness: 38 μm) to obtain an adhesive sheet. The obtained adhesive sheet was subjected to the above evaluation. The results are shown in Table 3.
[0207] [Comparative Example 3]
[0208] A resin composition was prepared in the same manner as in Production Example 1 except that a near infrared absorber (cesium tungsten oxide dispersion, trade name “YMF-02A”, manufactured by Sumitomo Metal Mining Co., Ltd.) was not added.
[0209] A laminate was obtained in the same manner as in Example 1 except that this resin composition was used instead of the second light-to-heat conversion layer-forming composition A to form a 5 μm thick resin layer. A pressure-sensitive adhesive sheet was further obtained. The obtained pressure-sensitive adhesive sheet was subjected to the above evaluation. The results are shown in Table 3.
[0210] [Comparative Example 4]
[0211] 100 parts by weight of carbon black-based black printing ink NB300 (manufactured by Dainichi Seika Co., Ltd.) and 5 parts by weight of isocyanate curing agent (manufactured by Dainichi Seika Co., Ltd., trade name "Lamic B Hardener") were mixed to prepare a second light-to-heat conversion layer-forming composition I. It should be noted that NB300 contains a polyurethane-based vinyl acetate-vinyl chloride copolymer as a binder resin, and an intensity peak believed to be urethane was confirmed by IR.
[0212] The second photothermal conversion layer-forming composition I was applied to one side of a polyethylene terephthalate film (manufactured by Toray Industries, Ltd., trade name "Lumirror S105", thickness: 25 μm) using a gravure coater so that the thickness after solvent volatilization (drying) was 0.2 μm, and then dried to obtain a laminate (second photothermal conversion layer / first photothermal conversion layer (substrate: polyethylene terephthalate film)).
[0213] An adhesive was applied to the first light-to-heat conversion layer (substrate) side of the laminate to form an adhesive layer with a thickness of 10 μm. In addition, an adhesive was applied to the second light-to-heat conversion layer side of the laminate to form an adhesive layer with a thickness of 30 μm. The obtained adhesive sheet was subjected to the above evaluation. The results are shown in Table 3.
[0214] It should be noted that the composition of the adhesive is the same as that of Example 1.
[0215] [Comparative Example 5]
[0216] The second photothermal conversion layer-forming composition II was prepared by mixing 100 parts by weight of carbon black-based black printing ink CVL-PR (manufactured by DIC Corporation) and 4 parts by weight of an isocyanate curing agent (manufactured by DIC Corporation, trade name "CVL Hardener No. 10"). It should be noted that CVL-PR contains a polyurethane-based vinyl acetate-vinyl chloride copolymer as a binder resin, and an intensity peak believed to be a urethane was confirmed by IR.
[0217] The second photothermal conversion layer-forming composition II was applied to one side of a polyethylene terephthalate film (manufactured by Toray Industries, Inc., trade name "Lumirror S105", thickness: 25 μm) using a gravure coater so that the thickness after solvent volatilization (drying) was 3 μm, and then dried to obtain a laminate (second photothermal conversion layer / first photothermal conversion layer (substrate: polyethylene terephthalate film)).
[0218] An adhesive was applied to the first light-to-heat conversion layer (substrate) side of the laminate to form an adhesive layer with a thickness of 10 μm. In addition, an adhesive was applied to the second light-to-heat conversion layer side of the laminate to form an adhesive layer with a thickness of 30 μm. The obtained adhesive sheet was subjected to the above evaluation. The results are shown in Table 3.
[0219] It should be noted that the composition of the adhesive is the same as that of Example 1.
[0220] [Table 1]
[0221]
[0222] [Table 2]
[0223]
[0224] [Table 3]
[0225]
[0226] As is apparent from Table 1, the pressure-sensitive adhesive sheet of the present invention has excellent visible light transmittance and exhibits debonding properties with respect to both IR laser light and UV laser light.
[0227] Description of symbols
[0228] 10. First light-to-heat conversion layer
[0229] 20 Second light-to-heat conversion layer
[0230] 30 Adhesive layer
[0231] 40 Another adhesive layer
[0232] 110 Adhesive sheet for temporary fixing of electronic components
Claims
1. An adhesive sheet for temporarily fixing electronic components, wherein: The adhesive sheet for temporarily fixing electronic components comprises: A stacked structure A, comprising a first light-to-heat conversion layer and a second light-to-heat conversion layer disposed on at least one side of the first light-to-heat conversion layer; and an adhesive layer, the adhesive layer being arranged on at least one side of the laminate structure A, The transmittance of the adhesive sheet for temporarily fixing electronic components to light with a wavelength of 1032 nm is 75% or less, and The pressure-sensitive adhesive sheet for temporarily fixing an electronic component has a transmittance of 50% or less at a wavelength of 355 nm.
2. The adhesive sheet for temporarily fixing electronic components according to claim 1, wherein The first light-to-heat conversion layer is a layer capable of absorbing ultraviolet rays.
3. The adhesive sheet for temporarily fixing electronic components according to claim 1, wherein The first light-to-heat conversion layer is made of polyimide resin, polyester resin or polyetheretherketone resin.
4. The adhesive sheet for temporarily fixing electronic components according to claim 1, wherein The 5% weight loss temperature of the first light-to-heat conversion layer is above 300° C.
5. The adhesive sheet for temporarily fixing electronic components according to claim 1, wherein The second light-to-heat conversion layer is a layer capable of absorbing near infrared rays.
6. The adhesive sheet for temporarily fixing electronic components according to claim 1, wherein The second light-to-heat conversion layer includes a near infrared absorber.
7. The adhesive sheet for temporarily fixing electronic components according to claim 6, wherein The near infrared absorber is a substance containing tungsten element.
8. The adhesive sheet for temporarily fixing electronic components according to claim 6, wherein The near infrared absorber is a substance containing cesium element.
9. The adhesive sheet for temporarily fixing electronic components according to claim 1, wherein The 5% weight loss temperature of the second light-to-heat conversion layer is above 300° C.
10. A method for processing an electronic component, wherein: An electronic component is disposed on the pressure-sensitive adhesive sheet according to any one of claims 1 to 9, and then the electronic component is subjected to a predetermined treatment.
11. The method for processing electronic components according to claim 10, wherein: The processing is grinding, cutting, chip bonding, wire bonding, etching, evaporation, chemical liquid cleaning, molding, redistribution layer formation, through hole formation or device surface protection.
12. A method for separating a temporarily fixed electronic component from a support, wherein: The separation method comprises: The pressure-sensitive adhesive sheet for temporarily fixing an electronic component according to any one of claims 1 to 9 is arranged on a support, The electronic component is arranged on the adhesive sheet for temporarily fixing the electronic component, and then, The adhesive sheet is irradiated with light to separate the first light-to-heat conversion layer from the second light-to-heat conversion layer.
13. The method for separating a temporarily fixed electronic component from a support according to claim 12, wherein: The light is laser.
14. The method for separating a temporarily fixed electronic component from a support according to claim 13, wherein: The wavelength of the laser is 800 nm or more.
15. The method for separating a temporarily fixed electronic component from a support according to claim 13, wherein: The wavelength of the laser is 380 nm or less.